We're going on a bear hunt - Rosen, Michael, 1946-; Oxenbury, Helen (New York : Margaret K. McElderry Books, 1989)
Brave bear hunters go through grass, a river, mud, and other obstacles before the inevitable encounter with the bear forces a headlong retreat.
Keywords: Bears -- Fiction; Hunting stories